2016
DOI: 10.5897/jvmah2015.0430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine trypanosomosis and its vector apparent density in Chora District of Illuababora Western Oromia, Ethiopia

Abstract: Bovine trypanosomosis is transmitted by tsetse and other biting flies which cause the most serious veterinary and animal production problem in sub-Saharan Africa. Cross sectional study was conducted from September to December, 2013 in Chora district, Western Oromia to assess the prevalence of trypanosomosis and apparent density of its vector. The methods employed during the study were deploying trap for the collection of tsetse flies and buffy coat technique for parasitological study. About 45 monopyramidal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
4
5
1
Order By: Relevance
“…Among the total (37) infected animals, 69.44 and 30.56% of them were anaemic and nonanaemic cattle, and the difference was statistically significant at P < 0.05. The result of this finding is in agreement with the finding of Marta et al [ 30 ] who reported that the highest prevalence of trypanosomosis from anaemic cattle in Chora districts of Oromia Region, Ethiopia. The higher prevalence of infected animal in association to being anaemic might be attributed to the sampled animals which got diseases such as helminthosis, tick-borne diseases, and nutritional imbalances, and it is in accordance to the suggestion provided by [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Among the total (37) infected animals, 69.44 and 30.56% of them were anaemic and nonanaemic cattle, and the difference was statistically significant at P < 0.05. The result of this finding is in agreement with the finding of Marta et al [ 30 ] who reported that the highest prevalence of trypanosomosis from anaemic cattle in Chora districts of Oromia Region, Ethiopia. The higher prevalence of infected animal in association to being anaemic might be attributed to the sampled animals which got diseases such as helminthosis, tick-borne diseases, and nutritional imbalances, and it is in accordance to the suggestion provided by [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…e result of this finding was almost in line with Adane and Gezahagne [27] who reported a 3.5% prevalence of trypanosomosis in Dejen district, Amhara Region, Ethiopia. e result of this finding was lower compared to other studies conducted somewhere else within the same country, which varies from 4.43 to 14.97% in a year between 2012 and 2019 [1,[28][29][30][31][32][33]. e overall low record of the prevalence of trypanosomosis may be due to the impact of parasite, and vector control practices have been working by Bedele NTTICC (Bedele National Tsetse and Trypanosomiasis Investigation and Control Centre) and the geographical location of the study areas, which have equal access for getting an extension service to the farmers regarding how to control the distribution of vectors (tsetse flies), disease control, and treatments used for treating the infected animal.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations